2022
DOI: 10.1111/aphw.12353
|View full text |Cite
|
Sign up to set email alerts
|

Psychological benefits of outdoor physical activity in natural versus urban environments: A systematic review and meta‐analysis of experimental studies

Abstract: The impact of environmental context on the psychological benefits derived from physical activity has attracted research attention in recent years. Previous reviews have compared effects of indoor versus outdoor exercise. This review compares the effects of physical activity undertaken in outdoor green natural environments versus outdoor urban environments on psychological health outcomes in adult general populations. An electronic literature search identified 24 experimental studies meeting the inclusion crite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(31 citation statements)
references
References 56 publications
2
28
1
Order By: Relevance
“…Importantly, exercise does not increase inflammation in them, on the contrary 60 . Of special biodiversity interest, although concerning adults, is a review of 24 experimental studies focusing on physical activity in different environments 61 . The meta‐analysis revealed favorable effects of the natural environment for anxiety, fatigue, vigor, and depression.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, exercise does not increase inflammation in them, on the contrary 60 . Of special biodiversity interest, although concerning adults, is a review of 24 experimental studies focusing on physical activity in different environments 61 . The meta‐analysis revealed favorable effects of the natural environment for anxiety, fatigue, vigor, and depression.…”
Section: Discussionmentioning
confidence: 99%
“…[ 10 , 11 , 12 ]. Indeed, a meta-analysis study showed that exposure to natural environments was associated with a moderate increase in positive affect and a smaller, yet consistent, decrease in negative affect relative to comparison conditions [ 13 , 14 ]. Additionally, lower immune activation was observed following social stress in rural compared to urban participants raised with regular or no animal contact, respectively [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the relationship between nature connection and mental well-being has been found in both the general population and those experiencing mental ill-heath [ 44 , 45 , 46 ], further demonstrating the potential importance of this construct. Whilst nature connection was not significantly associated with anxiety, previous research has proposed that the nature–health relationship may differ between mental health conditions [ 46 , 47 ]. Anxiety is more likely to be caused by things happening in the present moment, with different physiological effects from depression [ 48 , 49 ].…”
Section: Discussionmentioning
confidence: 99%